Platia Magoula Zarkou The Neolithic Period. Environment, Stratigraphy and Architecture, Chronology, Tools, Figurines and Ornaments (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
This volume of the publication of the excavations of the Neolithic tell of Platia Magoula Zarkou in Thessaly/Greece presents its continuous settlement sequence of the 6th millennium BC. Cultural change of this period is analysed based on its stratigraphy and constructions, the radiocarbon data, the tools, the ritual objects (including the house model) as well as the ornaments. Geological and geophysical investigations of the surroundings put the tell in its natural environment.